2017
DOI: 10.11157/sites-vol14iss1id378
|View full text |Cite
|
Sign up to set email alerts
|

Trouble on the Frontier: Hunt for the Wilderpeople, Sovereignty, and State Violence

Abstract: Beneath the hilarity of Taika Waititi’s Hunt for the Wilderpeople (2016) emerges a telling commentary on the increasingly normalised presence of paramilitarism in aspects of Aotearoa New Zealand’s society. In this essay, I use Waititi’s Hunt for the Wilderpeople as a lens through which to discuss the on-going nature of colonial violence directed towards the Ngāi Tūhoe people, exemplified in the 2007 ‘anti-terror’ raids codenamed ‘Operation 8’, and the more recent (but less well known) raids that have targeted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…In this chapter, I emphasize that positive peace in settler colonial contexts is unrealizable without meaningfully addressing the dispossession of land and the precipitated impacts of colonization upon Indigenous peoples. Drawing from my research on the New Zealand settler colonial state (Aikman, 2017(Aikman, , 2019, I demonstrate how structural and overt violence continues to typify Māori existence. By "settler colonial state," I am referring to a system of government, such as a Parliamentary democracy, founded upon the dispossession of Indigenous lands, peoples, and ways of life.…”
Section: Landed Sovereigntymentioning
confidence: 94%
See 4 more Smart Citations
“…In this chapter, I emphasize that positive peace in settler colonial contexts is unrealizable without meaningfully addressing the dispossession of land and the precipitated impacts of colonization upon Indigenous peoples. Drawing from my research on the New Zealand settler colonial state (Aikman, 2017(Aikman, , 2019, I demonstrate how structural and overt violence continues to typify Māori existence. By "settler colonial state," I am referring to a system of government, such as a Parliamentary democracy, founded upon the dispossession of Indigenous lands, peoples, and ways of life.…”
Section: Landed Sovereigntymentioning
confidence: 94%
“…The deployment of significant force by the state is, therefore, quintessential to the Crown's dealings with Māori over land in the past 150 years. In my recent research, I suggested these violent interactions demonstrate that Indigenous peoples and their sovereignties remain an existential threat to settler colonial existence (Aikman, 2017(Aikman, , 2019. The originary foundation of settler states rests upon the ongoing dispossession of Indigenous lands.…”
Section: Perpetual Indigenous Dispossessionmentioning
confidence: 99%
See 3 more Smart Citations